Adjuvant stereotactic body radiotherapy following transarterial chemoembolization in patients with non‐resectable hepatocellular carcinoma tumours of ≥3 cm. Issue 2 (February 2015) - Jacob, Rojymon; Turley, Falynn; Redden, David T.; Saddekni, Souheil; Aal, Ahmed K.A.; Keene, Kimberly; Yang, Eddy; Zarzour, Jessica; Bolus, David; Smith, J. Kevin; Gray, Stephen; White, Jared; et al.
Abstract: Objectives: The optimal locoregional treatment for non‐resectable hepatocellular carcinoma (HCC) of ≥3 cm in diameter is unclear. Transarterial chemoembolization (TACE) is the initial intervention most commonly performed, but it rarely eradicates HCC. The purpose of this study was to measure survival in HCC patients treated with adjuvant stereotactic body radiotherapy (SBRT) following TACE. Methods: A retrospective study of patients with HCC of ≥3 cm was conducted. Outcomes in patients treated with TACE alone ( n = 124) were compared with outcomes in those treated with TACE + SBRT ( n = 37). Results: There were no significant baseline differences between the two groups. The pre‐TACE mean number of tumours ( P = 0.57), largest tumour size ( P = 0.09) and total tumour diameter ( P = 0.21) did not differ significantly between the groups. Necrosis of the HCC tumour, measured after the first TACE, did not differ between the groups ( P = 0.69). Local recurrence was significantly decreased in the TACE + SBRT group (10.8%) in comparison with the TACE‐only group (25.8%) ( P = 0.04). After censoring for liver transplantation, overall survival was found to be significantly increased in the TACE + SBRT group compared with the TACE‐only group (33 months and 20 months, respectively; P = 0.02). Conclusions: This retrospective study suggests that in patients with HCC tumours of ≥3 cm, treatment with TACE + SBRT provides a survival advantage over treatment with only TACE. Confirmation of this observation requires that the concept be tested in a prospective, randomized clinical trial.